Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.21273/jashs.138.6.416
|View full text |Cite
|
Sign up to set email alerts
|

Leaf:fruit Ratio Affects the Proteomic Profile of Grape Berry Skins

Abstract: The most obvious effects of a low leaf:fruit (LF) ratio [two leaves for one cluster per shoot (LF2)] on grape (Vitis vinifera) berries are suppressed anthocyanin biosynthesis in the berry skin, decreased berry weight and soluble solids concentration, and increased titratable acidity. In this study, proteins isolated from berry skins grown under low and high LF ratio conditions, LF2 and LF12, respectively, were characterized by two-dimensional gel electrophoresis coupled to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Abiotic constraints are known to exert a negative effect on secondary metabolites, such as phenolic compounds [51]. Also, in our study, a competitive relationship between primary and secondary metabolites in berries was registered (Table 3), confirming other results reported previously [52,53]. In HD berries, the impact of natural hail might have inhibited phenolic biosynthesis and/or promoted phenolic degradation.…”
Section: Effect Of Natural Hail On Fruit Compositionsupporting
confidence: 91%
“…Abiotic constraints are known to exert a negative effect on secondary metabolites, such as phenolic compounds [51]. Also, in our study, a competitive relationship between primary and secondary metabolites in berries was registered (Table 3), confirming other results reported previously [52,53]. In HD berries, the impact of natural hail might have inhibited phenolic biosynthesis and/or promoted phenolic degradation.…”
Section: Effect Of Natural Hail On Fruit Compositionsupporting
confidence: 91%
“…After recalculation from the dataset of recent reports, we found that source limitation caused a 99.2% reduction in anthocyanins with a 38.5% reduction in sugars in cv. Jingyan ( Vitis vinifera ; Wu et al, 2013 ), and a 17.5 or 19.1% reduction in anthocyanins with a 8.4 or 6.8% reduction in sugars in cv. Sangiovese ( Pastore et al, 2011 , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent genome-wide transcriptome analyses showed that carbon limitation reduced the transcript abundance of UDP glucose:flavonoid-3- O -glucosyltransferase (UFGT) and GST4, which are known as important regulators of anthocyanin accumulation and transport ( Pastore et al, 2011 , 2013 ). A proteomic analysis showed that the abundances of chalcone synthase and dihydroflavonol reductase, which are both involved in anthocyanin pathway, were strongly reduced by source limitation ( Wu et al, 2013 ). Our observed reduction in total anthocyanin in both cultivars under source limitation should also result from modifications in the key regulators of anthocyanin pathways, although further transcriptomic and proteomic experiments are needed to confirm these speculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations